Vessel traffic safety in busy waterways: A case study of accidents in western shenzhen port. (February 2019) - Mou, J.M.; Chen, P.F.; He, Y.X.; Yip, Tsz Leung.; Li, W.H.; Tang, J.; Zhang, H.Z.
Highlights: High risk of vessel traffic in busy waterways requires Safety Indexes(SI) for management. Base on risk criteria, a framework of SI was proposed for vessel traffic, including Safety Evaluation Index (SEI) and Safety Warning Index (SWI). SEI acts as an indicator to measure safety status, while SWI acts as threshold to trigger actions of risk control. The risk criteria are developed by taking account of the accident severity, fatality rate, special indicators of maritime transportation and regional safety work status. Decade implementation of SI indicate the methodology can support the risk management in a macroscopic perspective for vessel traffic. Abstract: Throughout the world, busy waterways near large ports witness heavy vessel traffic in recent decades. The waterways are characterized by high risk in terms of loss of life, property, and pollution to environment. To facilitate maritime safety management with satisfactory efficiency and efficacy, the authors propose a framework of safety indexes to evaluate the risk level in busy waterways according to the accident severity, fatality rate and special indicators of maritime transportation. The safety indexes consist of Safety Evaluation Index (SEI) and Safety Warning Index (SWI), and are derived from the proposed risk criteria of Chinese vessel traffic. As a case study, data on vessel traffic accidents reported in the Western Shenzhen Port, South China from 1995 to 2015 are analyzed. The actual risk level of this area during the period is calculated under the framework. The implementation of the safety indexes indicate that the risk criteria and safety indexes are practicable and effective for the vessel traffic management. The methodology based on long-term accident data can significantly support the risk analysis in the macroscopic perspective for busy ports and waterways, such that SWI can act as threshold to trigger actions, while SEI can act as an indicator to measure safety status.